Altering dietary calcium does not influence tenderness in cattle fed Zilmax - C.L. Van Bibber-Krueger; K.A. Miller; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2013)
Tenderness is a key contributor to the sensory attributes of beef, and production practices that decrease tenderness are generally viewed as unfavorable. Zilmax (Merck Animal Health, Summit, NJ) is a potent beta-adrenergic agonist that results in dramatic improvements in carcass weight when fed to cattle, normally for a period of 20 days prior to harvest. Zilmax increases muscle mass at the expense of body fat, and these changes can have favorable effects on retail yield and overall value of beef carcasses. One of the unfavorable side effects of Zilmax is a decrease in meat tenderness. Aging of beef is one means of improving tenderness. During the aging process, proteolytic enzymes degrade the myofibrillar proteins that contribute to the perceptions of tough meat. Activity of these enzymes is stimulated by the presence of calcium ions, and various strategies aimed at increasing intracellular concentrations of calcium have been investigated as a means of improving beef tenderness. The purpose of this experiment was to determine if dietary calcium could be manipulated during the period of Zilmax supplementation as a means of improving meat tenderness. To do this, we eliminated supplemental calcium from the diet in hopes of inducing the secretion of parathyroid hormone. Parathyroid hormone stimulates the mobilization of calcium deposited in skeletal tissue, and we hypothesized that by decreasing dietary calcium we could potentially increase bone mobilization, and in so doing increase the supply of calcium available to proteolytic enzymes within skeletal muscle to enhance activity of these enzymes post-mortem.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; Calcium; Tenderness; Zilmax; Feedlot performance; Carcass characteristics